2021
DOI: 10.1038/s41598-021-82749-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dose-volume histogram prediction for organ-at risk and planning target volume based on machine learning

Abstract: The purpose of this work is to evaluate the performance of applying patient dosimetric information induced by individual uniform-intensity radiation fields in organ-at risk (OAR) dose-volume histogram (DVH) prediction, and extend to DVH prediction of planning target volume (PTV). Ninety nasopharyngeal cancer intensity-modulated radiation therapy (IMRT) plans and 60 rectal cancer volumetric modulated arc therapy (VMAT) plans were employed in this study. Of these, 20 nasopharyngeal cancer cases and 15 rectal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…One research group used two different methods, one based on the uniform field doses of nine equidistant IMRT beams and the other utilizing geometric information about relative target and OAR positions. 10 With similar results for the two methods the study found mean prediction errors across OARs of between 1% to 8% for nasopharyngeal cancer cases, and 2% to 6% for rectal cancer cases, compared to 0.3% to 3.7% for 50 Gy in five fractions and 0.3% to 7.6% for 54 Gy in three fractions in our study. Another approach also focusing on patients with nasopharyngeal cancer adopted multiple linear fitting of DVH metrics from various sub‐regions of OARs based on how far away each sub‐region is from the target.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…One research group used two different methods, one based on the uniform field doses of nine equidistant IMRT beams and the other utilizing geometric information about relative target and OAR positions. 10 With similar results for the two methods the study found mean prediction errors across OARs of between 1% to 8% for nasopharyngeal cancer cases, and 2% to 6% for rectal cancer cases, compared to 0.3% to 3.7% for 50 Gy in five fractions and 0.3% to 7.6% for 54 Gy in three fractions in our study. Another approach also focusing on patients with nasopharyngeal cancer adopted multiple linear fitting of DVH metrics from various sub‐regions of OARs based on how far away each sub‐region is from the target.…”
Section: Discussionsupporting
confidence: 84%
“…A recent study evaluated two different methods of DVH prediction for the treatment of nasopharyngeal cancer and rectal cancer. 10 The authors found that prediction of specific dose‐volume histogram (DVH) points was achievable within 5% accuracy for most of the studied OARs.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This could be remedied by using methods that can predict DVH for both target volumes and OARs. 34 , 35 Recent studies have also proposed methods to predict voxel‐based 3D dose distributions, 36 , 37 , 38 which are additional promising tools for plan quality control and assurance. Our future work may include building RapidPlan models from reoptimized plans according to multiple physician reviews such as ones collected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ML may also be used to propose risk factors for anastomotic leakage after esophagectomy [120]. Other attempts included using DL to identify optimal dosing of radiotherapy in GEA or defining the optimal target volume and organs at risk [121][122][123][124][125]. A dedicated analysis by Rahman et.…”
Section: Epidemiology Radiation Oncology and Blood Biomarkersmentioning
confidence: 99%